1998
DOI: 10.1089/thy.1998.8.43
|View full text |Cite
|
Sign up to set email alerts
|

Serum Concentration of Soluble Fas in Patients with Autoimmune Thyroid Diseases

Abstract: Fas is an apoptosis-signaling receptor molecule found on the surface of a number of cell types. Malfunction of the Fas system accelerates autoimmune diseases, whereas its exacerbation may cause tissue destruction. Soluble Fas (sFas) molecule lacks the transmembrane domain due to alternative splicing and blocks Fas-mediated apoptosis. This study investigated serum levels of sFas in autoimmune thyroid diseases. Serum levels of sFas were determined by enzyme-linked immunosorbent assay in 46 patients with Graves' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…They confirmed that serum sFas increases in GD and provided evidence of local production of sFas by thyrocytes and its regulation by cytokines. These studies suggest that sFas, by interfering with the Fas±FasL interaction, may also play a role in the pathogenesis of GD (38,39).…”
Section: Graves' Diseasementioning
confidence: 86%
See 2 more Smart Citations
“…They confirmed that serum sFas increases in GD and provided evidence of local production of sFas by thyrocytes and its regulation by cytokines. These studies suggest that sFas, by interfering with the Fas±FasL interaction, may also play a role in the pathogenesis of GD (38,39).…”
Section: Graves' Diseasementioning
confidence: 86%
“…The serum levels of sFas have recently been measured in patients with autoimmune thyroid diseases (38). In contrast to normal controls, sFas was increased in thyrotoxic patients with GD, but reduced in patients with GD in remission.…”
Section: Fas Ligand Expression In the Thyroidmentioning
confidence: 99%
See 1 more Smart Citation
“…Local immunosuppressive regulatory cytokines (TGF-β and IL-10) may be involved in the maintenance of tolerance and prevention of AITD [18,19] . A decreased apoptosis of activated T cells, like in defects of interaction of Fas (CD95) and Fas ligand (Fas-L), has been studied in AITD [20] . The proportion of intrathyroidal natural killer T cell subset has been found lower in GD than in the peripheral blood of the same patients and of controls, contributing to the incomplete regulation of autoreactive T cells [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Elevated blood concentration of sFas was observed in some autoimmune disease: systemic lupus erythematosus [15], cutaneous tuberculosis [4], Graves' disease [13], as well as in patients with myocarditis, heart failure [12], T and B cell leukemia [8], and hepatocellular carcinoma [61.…”
mentioning
confidence: 99%